Living high, training low: A new approach to altitude training at sea level in athletes - Rusko, H.; Leppävuori, A.; Makela, P.; Leppäluoto, J. (Medicine & Science in Sports & Exercise, 1995)
It is now accepted that training and living at high altitudes does not increase sea-level (SL) performance over that which results from training and living at SL. As a further machination on this "altitude-training-benefits theme," living high, training low (HiLo) has been suggested as the optimal strategy for using altitude effects to enhance performance at SL. This particular study used elite female cross-country skiers (N = 6) and compared a HiLo simulation strategy with normal altitude training (HiHi). Nitrogen was used to dilute ambient air in an apartment to simulate moderate altitude living at SL (15.3% O2 which is equivalent to 2500 m altitude). Ss lived in the apartment for 14 hours per day. Ss lived at SL for 11 days and then moved to live at 2200 m and train at 2800 m for 13 days. Highest values of erythropoietin (EPO), and 2,3 diphosphoglycerate (DPG) occurred on the ninth day measurement session of the HiLo condition. In the HiHi condition, measures of EPO actually fell, while DPG measures were constant. Reticulocyte numbers fell slightly in the HiHi condition and were significantly higher than either HiLo or HiHi values on return to SL. The HiHi condition did not maintain all the measures at the same level as the HiLo. There were no consistent patterns of effects of SL, HiLo, and HiHi conditions on all the variables. It is prudent to conclude that there was no "effect" demonstrated although variations were evident in all three measures. Those variations could easily have resulted from a lack of experimental control. However, in the study it was arguably concluded that the simulation was successful and that all subjects demonstrated stimulated erythropoiesis. The values reported in the article (see table below), did not demonstrate that which the authors concluded.